SUSTAINABLE QUAD HELIX DALAM PROGRAM KAMPUNG BATIK REJOMULYO DI KOTA SEMARANG - Amni Zarkasyi Rahman; Diyah Novitasari (Magister Administrasi Publik, FISIP, 2019)
The thematic village is one of the poverty eradication programs based on communityempowerment by promoting sustainable development and the creative economy, whichis implemented by the Semarang City Government. One of the successful ThematicVillages is the Batik Village of Rejomulyo, which is now one of the tourism icons ofSemarang City. The success of Batik Village Rejomulyo is inseparable from the role ofstakeholders. It takes a relationship and synergy between the university-industrygovernment-community so that the Batik Rejomulyo Village can develop until now. TheSemarang City Government, which encouraged the rise of the batik industry by makingRejomulyo as the Kampung Batik, made the community motivated to continue to becreative and to innovate. However, the relationship between industry and universitieswith government and society is still not well seen. Therefore, it is necessary to explorethe role of each stakeholder in the quad helix relationship so that the universityindustry-government-society can have a mutually beneficial and supportive mutualrelationship.